(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the main changes in the morphology of the Uzbek language. The changes are evident in word formation, affixes, and the syntactic and semantic transformations of word classes. The historical development of morphology is also discussed. The article examines the impact of social and cultural factors in the development of the language, including the emergence of new words, affixes, and syntactic structures